2021
DOI: 10.1002/lno.11786
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected shift from phytoplankton to periphyton in eutrophic streams due to wastewater influx

Abstract: Pollution with nitrogen (N) and phosphorous (P) impairs streams by favoring suspended algae and cyanobacteria over diatom-rich periphyton. Recently, wastewater treatment plants have been upgraded to biological nutrient removal to eliminate both P and N (mainly NH 4 +), although little is known of the effects of this effluent on flowing waters. Here, we used high performance liquid chromatography to quantify how the abundance and composition of phytoplankton and periphyton varied in response to both influx of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 71 publications
(192 reference statements)
1
2
0
Order By: Relevance
“…Although turbidity occasionally enters predictive models elsewhere (Rome et al 2021), to the best of our knowledge, ours is the first model with turbidity as the main parameter that exhibits performance comparable to that of fluorescence‐based models. This finding is consistent with the observation that phytoplankton abundance controls turbidity measures in regional lakes and streams (Dröscher et al 2009; Bergbusch et al 2021), although we recognize that this finding may not apply when nonalgal turbidity is considerable. As turbidity probes are inexpensive, robust, and easy to calibrate relative to fluorometric sensors (Rome et al 2021), the strong performance of the MLR model should be compared to other locations to evaluate the suitability in monitoring phytoplankton blooms.…”
Section: Discussionsupporting
confidence: 92%
“…Although turbidity occasionally enters predictive models elsewhere (Rome et al 2021), to the best of our knowledge, ours is the first model with turbidity as the main parameter that exhibits performance comparable to that of fluorescence‐based models. This finding is consistent with the observation that phytoplankton abundance controls turbidity measures in regional lakes and streams (Dröscher et al 2009; Bergbusch et al 2021), although we recognize that this finding may not apply when nonalgal turbidity is considerable. As turbidity probes are inexpensive, robust, and easy to calibrate relative to fluorometric sensors (Rome et al 2021), the strong performance of the MLR model should be compared to other locations to evaluate the suitability in monitoring phytoplankton blooms.…”
Section: Discussionsupporting
confidence: 92%
“…This contrasts our previous findings that primary production was not a significant driver of seasonal CO 2 concentrations in constructed reservoirs (Jensen et al., 2022), and may reflect difference in the relative control of autotrophic and heterotrophic control on temporal (Jensen et al., 2022) and spatial scales (this paper). The coupling of near‐surface CO 2 in reservoirs with DOC:NO x ratios, suggests that higher autotrophic activity depletes NO x content in this N‐limited region (Bergbusch et al., 2021; Glibert et al., 2016; Swarbrick et al., 2019; Waiser et al., 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Not only can the benthic algae contribute to productivity, but they can also produce cyanotoxins in rivers (Bouma‐Gregson et al., 2018). Recent research has demonstrated that effluent can shift systems from phytoplankton to periphyton communities (Bergbusch et al., 2021) and not accounting for benthic algae could miss important periods of algal activity in some systems. Adding information on benthic algae would help capture more spatial and temporal variability in stream productivity, water quality, and ecosystem health across streams and rivers.…”
Section: Discussionmentioning
confidence: 99%